Determinants Of Premenstrual Syndrome And Premenstrual Dysphoric Disorder In Adolescent In Covid-19 Era - Dewi, Tri Kesuma; Utami, Indhit Tri (Sean Institute, 2022)
This pandemic has resulted in many changes, one of which is online learning. This change causes increased stress on students. In women, stress is one of the factors causing the symptoms of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD). Women who experience PMS and PMDD will interfere with daily activities and interfere with social relationships. The occurrence of PMS and PMDD will reduce the quality of life of adolescents and will result in disrupted learning processes, so we need to know whether the pandemic affects the increase in PMS and PMDD so that we can determine preventive measures. This needs to be done considering that this pandemic will continue and we need to adapt to these changes. This study aims to see if there is a difference in the prevalence of premenstrual syndrome and premenstrual dysphoric disorder before and after the pandemic occurs and to find out what factors can influence it.This study will use quantitative research methods with a cross sectional approach. Data collection will be carried out at three high schools, namely public, private and high schools with dormitories. Determination of schools using simple random sampling technique and for respondents using total sampling. The sample in this study amounted to 252 students in grade 3 SMA. This data collection is done by filling out a questionnaire. Data collection was carried out after the researchers determined the school as the research location and permission was obtained. The data that has been collected will be processed using SPSS 21. Data analysis will use univariate, bivariate and multivariate data analysis. In this study, the factors that did not affect the occurrence of PMS/PMDD in adolescents were coffee consumption, calcium, body weight and heredity. The factor that influences the occurrence of PMS and PMDD is stress with a P-value of 0.000. Stress is a determining factor in the occurrence of PMS or PMDD in adolescents, students, teachers and health workers should collaborate in dealing with stress in adolescents, especially during the COVID-19 pandemic.